PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. MITRA HOSINDO SEJAHTERA - ELFRIDA FITRIANA L; MAULI SIAGIAN (JURNAL ILMIAH KOHESI, 2020)
This study aims to determine the effect of discipline and work motivation on the performance of employees of PT MitraHosindo Sejahtera. There is no doubt that work discipline and motivation are factors that can affect employee performance.Increasing discipline and work motivation will have a positive impact on employee performance. The research sampleidentified 100 employees of PT Mitra Hosindo Sejahtera. The way to gather information for research is by distributingquestionnaires to all employees. Data analysis methods for diagnostic tools, which include validity, reliability testing,standard assumptions, and hypothesis testing including T-tests and F-tests. The research tool used to process and analyzethis analytic data is SPSS version 26.0. The results showed that discipline has a positive and significant impact on employeeperformance. Work motivation has a positive and significant impact on employee performance. At the same time disciplineand work motivation are very influential in improving employee performance.